The Impact of Primary Care Dual-Management on Quality of Care - Peter J. Kaboli MD, MS; Daniel M. Shivapour MD; Michael S. Henderson MS; Areef Ishani MD; Mary E. Charlton PhD, RN (SAGE Publishing, 2012)
Background : Discontinuity is common in US healthcare. Patients access multiple systems of care and in the nation's largest integrated healthcare system, Veteran's Administration (VA) patients frequently use non-VA primary care providers. The impact of this "dual-management" on quality is unknown. The authors' objective was to identify dual-management and associations with markers of care quality for hypertension and associated conditions. Methods : Data was collected via surveys and chart reviews of primary care patients with hypertension from six VA clinics in Iowa and Minnesota. Clinical measures abstracted included the following: goal blood pressure (BP) and use of guideline-concordant therapy, low-density lipoprotein (LDL) cholesterol, hemoglobin A1C, and body mass index (BMI). Dual-management data was obtained through self-report. Results : Of 189 subjects (mean age = 66), 36% were dual-managed by non-VA providers. There was no difference in hypertension quality of care measures by dual-management status. A total of 51% were at BP goal and 58% were on guideline-concordant therapy. Dual-managed patients were more likely to use thiazide diuretics (43% vs 29%; P = .03) and angiotensin receptor blockers (13% vs 3%; P < .01), but less likely to use angiotensin-converting enzyme inhibitors (43% vs 61%; P = .02). There was no difference in LDL cholesterol (97.1 mg/dl vs 100.1 mg/dl; P = .55), hemoglobin A1C (7% vs 6%; P = .74), or BMI (29.8 vs 30.9; P = .40) for dual-managed versus VA managed patients, respectively. Conclusions : Although dual-management may decrease continuity, VA/private sector dual-management did not impact quality of care, though some medication differences were observed. With the high prevalence of dual-management, future work should further address quality and evaluate redundancy of services.